2022
DOI: 10.1093/g3journal/jkac311
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction of hybrid performance for agronomic traits in sorghum

Abstract: Hybrid breeding in sorghum [Sorghum bicolor (L.) Moench] utilizes the cytoplasmic nuclear male sterility (CMS) system for seed production and subsequently harnesses heterosis. Since the cost of developing and evaluating inbred and hybrid lines in the CMS system is costly and time consuming, genomic prediction of parental lines and hybrids based on genetic data would reduce breeding cycle length and increase probability of recovering exceptional product genotype. We generated 602 hybrids by crossing two female … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The prediction accuracies for days to mid-anthesis and grain yield ( Figure 4 ) are like those reported in other studies in sorghum [ 5 , 15 , 16 , 20 , 21 , 22 , 23 ]. However, the prediction accuracies for plant height are lower than in previous studies, much like what was observed by Winans et al [ 5 ] and Sapkota et al [ 22 ]. From observation, there is a large amount of variation in plant height, and it is likely that a few of the families are segregating for major dwarfing genes.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The prediction accuracies for days to mid-anthesis and grain yield ( Figure 4 ) are like those reported in other studies in sorghum [ 5 , 15 , 16 , 20 , 21 , 22 , 23 ]. However, the prediction accuracies for plant height are lower than in previous studies, much like what was observed by Winans et al [ 5 ] and Sapkota et al [ 22 ]. From observation, there is a large amount of variation in plant height, and it is likely that a few of the families are segregating for major dwarfing genes.…”
Section: Discussionsupporting
confidence: 85%
“…From observation, there is a large amount of variation in plant height, and it is likely that a few of the families are segregating for major dwarfing genes. Studies reporting high prediction accuracy for plant height had lines subject to more intense selection pressure, and it is likely that large-effect genes that control height were fixed [ 16 , 21 , 23 ], whereas studies with large variation in height, exotic germplasms, and minimal selection reported lower prediction accuracies [ 5 , 22 ]. Within this study, the GBLUP approach is limited in its ability to capture large single gene effects due to the distributed weight of effects across the genome [ 11 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heterotic grouping of hybrid parental lines and heterosis prediction in hybrids are the priority focus for increased heterosis to realize a significant jump in the productivity of pearl millet and sorghum. Some attempts have been made to define heterotic groups both in pearl millet and sorghum (Maulana et al, 2023;Pucher et al, 2018;Ramya et al, 2018;Sapkota et al, 2023). A study involving 320R and 260B Indian pearl millet parents identified two distinct heterotic groups from each group based on the heterotic performance and combining ability (S. K. Gupta et al, 2020).…”
Section: Improving Productivity To Make Millets Competitivementioning
confidence: 99%
“…This study also indicated that distinct parental groups could be formed based on molecular markers, which can help in assigning hybrid parental lines into appropriate heterotic groups to develop high-yielding hybrids. In sorghum, Sapkota et al (2023) phenotyped 602 hybrids for agronomic performance and genotyped their two female and 301 restorer male parents using 2.69 million single nucleotide polymorphisms for genomic prediction. Genomic best linear unbiased prediction showed that the agronomic performance of hybrids can be predicted with high accuracy, while the prediction of general combining ability of male parents varied from 0.33 to 0.62 for Crop Science different traits.…”
Section: Improving Productivity To Make Millets Competitivementioning
confidence: 99%